RURAL-URBAN MIGRANTS’ SENSE OF PLACE IN THE CITY OF BAODING, CHINA - Qingjiu, Sun; Maliki, Nor Zarifah (PLANNING MALAYSIA, 2018)
From 1978 to 2015, China’s urbanization rate raised from 17.92% to 56.10%. The rapid urbanization and urban development brought enormous changes in China. Rural-urban migration, the main driver of urban growth in the past few years, has changed the social, spatial, and economic landscapes of Chinese cities but also made the urban scene much more diverse, lively, and dynamic. After migrating to the city, the Chinese migrants are not only subject to difficulties in material aspects of surviving and socializing but also faced with predicaments in re-establishing psychological bonding with the urban environment; due to institutional obstacles such as the household registration system. This paper aims to explore the association between migrants’ sense of place and the institutional factor – household registration system. ’Sense of place’ is used as a lens to explore and explain migrants’ interconnections with the city.